Routine Blood Profiles of Global Ischemic Rats Based on Ischemia Durations - Rika Yulita Rahmawati; Utami Mulyaningrum; Ety Sari Handayani (EKSAKTA: Journal of Sciences and Data Analysis, 2022)
Stroke is the third cause of death and the first cause of disability in the world. It is around 80% of stroke patients in the world are ischemic stroke. According to the development of stroke models in animals, BCCAO is one technique that can induce global cerebral ischemia. An ischemia is known to influence activities of inflammatory cells which can be measured through peripheral blood. This study aims to determine effects of ischemia duration on routine blood profiles of rats (Rattus norvegicus) after bilateral common carotid artery occlusion (BCCAO). This study was a quasi-experimental study. Its subjects were adult Wistar rats (Rattus norvegicus). The rats were grouped into four treatment groups, and each group consisted of 6 rats. Group A was a group of sham-operated rats, group B was a group of rats with ischemia duration for 5 minutes, group C was a group of rats with ischemia duration for 10 minutes, and group D was a group of rats with ischemia duration for 20 minutes. Its obtained data were analysed by one-way ANOVA test and Post Hoc Tamhane's test. The ischemia duration significantly influenced the neutrophil and lymphocyte count after ischemia, with p < 0.05. The ischemia duration could affect the routine blood profiles of the rats after BCCAO, especially the neutrophil and lymphocyte count.